Argument Structure and Word Order in Saudi Sign Language - Altamimi, Haya S.; Alsager, Haroon N. (Journal of language teaching and research, 2023)
This study focuses on the description of argument structure and word order in Saudi Sign language (SSL). The nature of the syntactic level of the grammar of SSL is clarified. Since word order is often considered the most important part of grammar, this study details the various options that are available for the major constituents (Subject, Verb, and Object) in SSL independent of any connection to spoken Arabic syntax. In SSL, like in other languages, the nature of the arguments (Subject, Object) and the kind of verb can impact the word order. To investigate word order in SSL, which is based on Chomsky’s (1995) Minimalist Program (MP), data were collected through derivation of data from narratives (semi-naturalistic-corpus) and an experiment (picture-description task). This research involved a sample of 10 deaf signing participants who are all fluent in SSL. All the participants have lived in Saudi Arabia for at least 10 years. Results indicate that the SSL is as any natural language and from the spoken language in Saudi Arabia. The most common word order in declaratives and the basic constituent order in SSL is SVO. As in virtually all sign languages, Wh-elements in SSL occur at the end of the clause. According to research on the interaction between word order and grammatical use of facial expressions and head locations (nonmanual marking), nonmanual markings have pragmatic purposes and may have syntactic functions.